2021
DOI: 10.21873/anticanres.15277
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Can Predict Prognosis After Hepatectomy in Patients With Colorectal Liver Metastasis

Abstract: Background/Aim: The aim of this study was to investigate frailty as a prognostic factor in patients with colorectal liver metastasis undergoing hepatectomy. Patients and Methods: Eighty-seven patients who underwent hepatectomy at our institution were enrolled. Frailty was defined as a score of ≥4 on a clinical frailty scale. Patients were divided into frailty (n=29) and non-frailty (n=58) groups. Results: Overall and cancer-specific survival rates were significantly worse in the frailty group compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The OS of the CFS score 1-2 group was significantly higher than that of the CFS score 3-7 group (P = .01). CFS, Clinical Frailty Scale; OS, overall survival cutoff value of CFS varied among studies, 4,5,11,16 and even in this study, there is a difference in cutoffs for predicting prognosis and the development of complications. This may be due to differences in the impact of frailty on clinical outcomes, and we consider that a different cutoff value for each outcome may allow for a more rigorous evaluation.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The OS of the CFS score 1-2 group was significantly higher than that of the CFS score 3-7 group (P = .01). CFS, Clinical Frailty Scale; OS, overall survival cutoff value of CFS varied among studies, 4,5,11,16 and even in this study, there is a difference in cutoffs for predicting prognosis and the development of complications. This may be due to differences in the impact of frailty on clinical outcomes, and we consider that a different cutoff value for each outcome may allow for a more rigorous evaluation.…”
Section: Discussionmentioning
confidence: 60%
“…Although the CFS is a semiquantitative scale that does not include preoperative test results, it provides a more detailed assessment, including cognitive function, than the ECOG‐PS, and various studies have reported an association between CFS and clinical outcomes 4,5,11,16,28 . The cutoff value of CFS varied among studies, 4,5,11,16 and even in this study, there is a difference in cutoffs for predicting prognosis and the development of complications. This may be due to differences in the impact of frailty on clinical outcomes, and we consider that a different cutoff value for each outcome may allow for a more rigorous evaluation.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations